1999
DOI: 10.1007/bf02496276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,3,4-oxazaphospholines based on phosphorylated carbamates

Abstract: Addition of alcohols to bis(chloromethyl)phosphinoyl isoeyanate, as well as the re.action of bis(chloromethyl)phosphinoyl chloride with urethanes or their silylated derivatives, gave the corresponding phosphorylated carbamates which undergo cyclization into 1,3,4-oxazaphospholines under the action of Et3N.Key words: bis(chloromethyl)phosphinoyl chloride(isocyanate), phosphorylated carbamates, heterocyciization, 1,3,4-oxazaphospholines.At present, we are developing methods for the synthesis of polyheterophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Another synthetic option is the reaction of PCl3 with N-chloroamides of carbonic acid ROC(O)NHCl or N-chloroaminoethers (RO)2C=NCl leading to ROCON=PCl3 which can undergo hydrolysis to yield N-dichlorophosphoryl carbamates [3]. The range of synthetic methods was enlarged when it turned out that unsubstituted phosphorylated carbamates can be formed when phosphorylated isocyanates react with alcohols or mercaptanes [4]. This method can be applied for the synthesis of various types of phosphorylated carbamates.…”
Section: Introductionmentioning
confidence: 99%
“…Another synthetic option is the reaction of PCl3 with N-chloroamides of carbonic acid ROC(O)NHCl or N-chloroaminoethers (RO)2C=NCl leading to ROCON=PCl3 which can undergo hydrolysis to yield N-dichlorophosphoryl carbamates [3]. The range of synthetic methods was enlarged when it turned out that unsubstituted phosphorylated carbamates can be formed when phosphorylated isocyanates react with alcohols or mercaptanes [4]. This method can be applied for the synthesis of various types of phosphorylated carbamates.…”
Section: Introductionmentioning
confidence: 99%
“…155!156. Proceeding with the development of synthetic approaches to new heterophosphacyclanes with endocyclic P3C bonds on the basis of functional a-substituted alkylphosphonates [4,5], we explored ÄÄÄÄÄÄÄÄÄÄÄÄ the reactions of diphenyl a-(phenylamino)benzylphosphonate I with aromatic and phosphorylated iso-(thio)cyanates. Pudovik, L.K.…”
mentioning
confidence: 99%
“…Previously we showed that phosphorylated carbamates in the presence of bases undergo heterocyclization due to intramolecular interaction of the chloromethyl and carbonyl groups to form unsaturated heterocycles, such as 1,3,2-oxazaphospholines [2]. Aiming at preparing new functionalyzed (chloromethyl)phosphonates and (chloromethyl)thiophosphonates capable of further transformations, we reacted (chloromethyl)iso(thio)cyanatophosphonates-(-phosphinates) with phenol, ethanol, and thiols.…”
mentioning
confidence: 99%